A practitioner's perspective on psychological issues in football. Issue 2 (3rd April 2019) - Heidari, Jahan; Pelka, Maximilian; Beckmann, Jürgen; Kellmann, Michael
ABSTRACT: The challenges for professional football players are becoming more and more complex due to the multifaceted physical, technical, and psychological demands of the modern game. Psychological components have especially attracted the attention of science and are finding their way into practice. This overview article aims to discuss five psychological issues in football which the authors consider to be among the most relevant for sport-psychological practitioners. Each topic is structured identically: (a) topic description, (b) empirical evidence highlighting its relevance in football and potential impacts on performance, and (c) practical recommendations. The first two topics focus on the environment in football by discussing (1) organisational issues and (2) player–coach–parent triads within football teams. Subsequently, the central theme performance is evaluated. (3) How do health and well-being impact long-term elite performance? (4) How can the training of psychological skills enhance performance? (5) How does "choking under pressure" affect performance? It can be stated that sport-psychological football research has provided several important and meaningful findings so far which can partly be adapted to practical settings. An even stronger focus of research in applied settings is warranted to gain further insights into the psychological underpinnings prevalent in the world of football. From a practical perspective, the article may provide both researchers and practitioners with valuable input on selected psychological topics in football. The summarised research can serve as a starting point for further research or interventions in practical settings.